Racing wheels` effect on drag/side forces acting on a cyclist at sportstech-miun wind tunnel - Petrone, N.; Giacomin, M.; Koptyug, A.; Bäckström, M. (Proceedings, 2018)
The wind tunnel at the SportsTech Research Centre at Mid Sweden University (MIUN, Ostersund) was opened in 2015 for sports technology research. It is dedicated to analysis of equipment performance and garment development and suitable for roller skiing, running and cycling. The aim of this work was to develop and apply a full-scale method to investigate the aerodynamic behaviour of a cyclist facing front and cross wind at different yaw angles (from 0° to 30°) and speeds. To reach this goal, a rotating structure supported by a force platform was constructed. It includes a set of rollers on which fully unrestrained cycling is possible. The method was applied to the comparison of three wheelsets (differing in material, height and shape of the rim, number and shape of spokes) in terms of drag and side aerodynamic forces during a cyclist`s ride at 30 km/h, while keeping all the other factors constant. Resulting curves allowed estimating differences of 4% and 9% when applied to a recent time trial competition with supposed wind conditions.